Sudut Pandang Islam Tentang Perjalanan dan Tujuan Hidup Manusia - Sari Dewi Sinta; Siti Aminah; Mutia Safitri; Amelia Putri Andriani; Wismanto Wismanto (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This journal discusses the journey and purpose of human life from an Islamic perspective. It aims to provide more understanding about human life spiritually according to Islamic teachings. The study draws on various primary and secondary sources, including the Quran, which is the holy book revealed to mankind through the Prophet Muhammad, and the hadith. An interdisciplinary approach is used to integrate Islamic concepts with modern scientific understanding of human life. The study explores the meaning of ethics, virtue, and blessings in an Islamic perspective on the human life journey. It highlights the importance of living a life of good morals and benefitting others, with the aim of achieving success, happiness, and a good afterlife. The findings can deepen people's understanding of the purpose of life and inspire them to live a charitable and pious lifestyle, and not to be a vain creation of Allah but to be His Khalifah on earth.